2021
DOI: 10.1186/s40550-021-00082-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of beef carcass contamination with Salmonella and E. coli O 157 in slaughterhouses in Bishoftu, Ethiopia

Abstract: Background Salmonella and E. coli O157 are common causes of foodborne diseases. Evisceration and de-hiding steps can lead to carcass contamination during slaughter operation. In Ethiopia, information on the association between the presence of these pathogens in the rectal content and/or on the hide of cattle and their presence on the carcass is lacking. Methods The aim of this study was to assess the sources of beef carcass contamination with Salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
(41 reference statements)
3
10
1
Order By: Relevance
“…This is probably the result of cross-contamination during slaughter, which can occur with intestinal damage, faecal contamination, or contamination from the environment, equipment, or workers’ hands ( 43 ). Similarly, cattle carcass swabs were probably contaminated with E. coli during hide removal and evisceration ( 20 ). Other samples such as minced meat and meat preparations were contaminated during the slaughter process or subsequent handling ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably the result of cross-contamination during slaughter, which can occur with intestinal damage, faecal contamination, or contamination from the environment, equipment, or workers’ hands ( 43 ). Similarly, cattle carcass swabs were probably contaminated with E. coli during hide removal and evisceration ( 20 ). Other samples such as minced meat and meat preparations were contaminated during the slaughter process or subsequent handling ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Gutema et al (2021) showed that of the 8.6% of bovine carcasses that were contaminated with Salmonella spp., only a few were contaminated with the same strain as that isolated from rectal swabs of those animals. The authors concluded that, for the most part, contamination of carcasses by this microorganism was more related to cross-contamination than to contamination with the fecal content of the animal itself.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Gebremedhin et al [ 65 ] discovered that all tested S. typhimurium were highly sensitive to cefotaxime (85%), gentamycin (80%), amikacin (75%), and ciprofloxacin (60%). Furthermore, Gutema et al [ 66 ] and Jaja et al [ 67 ] found that the resistance pattern of S . typhimurium in beef samples was 100% for ampicillin and sulphamethoxazole in Ethiopia and South Africa, respectively.…”
Section: Discussionmentioning
confidence: 99%